2001
DOI: 10.2307/3871281
|View full text |Cite
|
Sign up to set email alerts
|

bus, a Bushy Arabidopsis CYP79F1 Knockout Mutant with Abolished Synthesis of Short-Chain Aliphatic Glucosinolates

Abstract: A new mutant of Arabidopsis designated bus1-1 (for bushy), which exhibited a bushy phenotype with crinkled leaves and retarded vascularization, was characterized. The phenotype was caused by an En-1 insertion in the gene CYP79F1. The deduced protein belongs to the cytochrome P450 superfamily. Because members of the CYP79 subfamily are believed to catalyze the oxidation of amino acids to aldoximes, the initial step in glucosinolate biosynthesis, we analyzed the level of glucosinolates in a CYP79F1 null mutant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
171
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(186 citation statements)
references
References 0 publications
13
171
2
Order By: Relevance
“…This result provides genetic confirmation for the partial functional redundancy of these two genes in glucosinolate metabolism and demonstrates that disruption of both genes results in the complete absence of aliphatic glucosinolates in the plant. It has previously been shown that indole glucosinolates are also increased in the sps/cyp79F1 mutant (Reintanz et al, 2001;Chen et al, 2003). However, the double knockout in both SPS/CYP79F1 and CYP79F2 genes did not significantly enhance biosynthesis of indole glucosinolates as compared to the single knockout in SPS/CYP79F1 gene (Table I).…”
Section: Generation Of Sps/cyp79f1 and Cyp79f2 Double Mutants By Multmentioning
confidence: 74%
See 3 more Smart Citations
“…This result provides genetic confirmation for the partial functional redundancy of these two genes in glucosinolate metabolism and demonstrates that disruption of both genes results in the complete absence of aliphatic glucosinolates in the plant. It has previously been shown that indole glucosinolates are also increased in the sps/cyp79F1 mutant (Reintanz et al, 2001;Chen et al, 2003). However, the double knockout in both SPS/CYP79F1 and CYP79F2 genes did not significantly enhance biosynthesis of indole glucosinolates as compared to the single knockout in SPS/CYP79F1 gene (Table I).…”
Section: Generation Of Sps/cyp79f1 and Cyp79f2 Double Mutants By Multmentioning
confidence: 74%
“…In addition, disruption of CYP83B1 function also up-regulates Trp biosynthesis and other stressinduced pathways (Smolen and Bender, 2002). Likewise, characterization of the bushy/sps/cyp79F1 mutants has shown that disrupting the SPS/CYP79F1 gene required for the synthesis of short-chain and long-chain aliphatic glucosinolates severely affects hormone homeostasis (Hansen et al, 2001;Reintanz et al, 2001;Tantikanjana et al, 2001). Despite the fact that sps/cyp79F1 mutants have higher level of both auxin and cytokinin, the mutants resemble plants with cytokinin overproduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with the higher expression levels of CYP74B2 (HPL) transcripts and volatiles produced, these data suggest that the levels of JAs are also elevated in Ler leaves compared to Col leaves. Also interesting among the set more highly expressed in the Ler ecotype are several loci in aliphatic glucosinolate synthesis, including CYP79F1, which exists upstream of CYP83A1 (Hansen et al, 2001;Reintanz et al, 2001;Chen et al, 2003), CYP83A1 itself, and 2-oxoglutarate-dependent dioxygenase (AOP3), which exists downstream of CYP83A1 (Kliebenstein et al, 2001b); Trp synthetase (TSB2; Last et al, 1991) also potentially impacts aliphatic glucosinolate synthesis because it is postulated to feed substrates into the aliphatic glucosinolate pathway via CYP79B2 and CYP79B3 . Contrasting with these glucosinolate synthetic enzymes that are more highly expressed in the Ler ecotype, one locus more highly expressed in the Col ecotype codes for thioglycosyl hydrolase (TGG2, myrosinase), which degrades glucosinolates to release toxic derivatives (Xue et al, 1995).…”
Section: Transcript Profiling In Col and Ler Ecotypesmentioning
confidence: 99%